Ultrathin TiO2 nanosheets synthesized using a high pressure solvothermal method and the enhanced photoresponse performance of CH3NH3PbI3–TiO2 composite films. Issue 34 (11th April 2017) - Jiao, Shilong; Fu, Xianwei; Lian, Gang; Jing, Laiying; Xu, Zhenghao; Wang, Qilong; Cui, Deliang
Abstract : Highly crystalline ultrathin (2–3 nm) TiO2 nanosheets are synthesized using a high pressure solvothermal method. The perovskite–TiO2 films exhibit strikingly enhanced photoresponse performance. Abstract : In perovskite–TiO2 composite optoelectronic devices, a large grain size, a high percentage of {001} facets, TiO2 nanocrystals with high crystallinity, and good interconnectivity between both TiO2 and perovskite particles are crucial for the excellent performance of a hybrid photodetector. In this work, a high pressure hydrothermal method was developed to synthesize highly crystalline ultrathin (2–3 nm) TiO2 nanosheets bound with a high percentage of {001} facets. When these TiO2 nanosheets were utilized in the fabrication of perovskite–TiO2 composite photodetectors, a strikingly increased responsivity and detectivity were achieved. Furthermore, when the films were subjected to high pressure thermal treatment, both the particle size and the uniformity of the composite films greatly increased, resulting in a better performance of the hybrid photodetectors.